Effects of Post-Treatment on the Microstructure Evolution and High-Temperature Oxidation Properties of Nickel-Based Superalloys Fabricated by Selective Laser Melting - Rui Ren; Yunxia Yao; Dongsheng Han; Jun Fang; Cai Chen (Metals)
This study mainly investigates the high-temperature oxidation properties of GH3230 alloys fabricated by selective laser melting after different heat treatments. The SLM-formed GH3230 samples were subjected to solid-solution treatments at 1100 °C, 1230 °C, and 1320 °C for 30 min, followed by water quenching to room temperature. High-temperature oxidation tests were conducted at 1100 °C for 100 h. The results show that the as-built sample is composed of many columnar grains with cellular dendrites. Many M23C6 carbides are distributed in the interdendritic of the as-built sample. After solid-solution treatment, the dendrite structures completely disappear and the M23C6 carbides are transformed into M6C carbides. The M6C carbides dissolve completely as the solid-solution temperature increases to 1320 °C. The average grain size of GH3230 samples increased gradually with the increase in the solid-solution treatment temperature. However, the degree of recrystallization increased with the heat treatment temperature, leading to the transformation of low-angle grain boundaries into high-angle grain boundaries. A relatively dense oxide film, mainly including Cr2O3 and CrMn2O4, are formed in the GH3230 alloy after high-temperature oxidation. Suitable solid-solution treatment improves the high-temperature oxidation resistance of the GH3230 alloy, and the enhanced oxidation-resistance mechanisms are discussed.